2020
DOI: 10.21203/rs.3.rs-113633/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infection Was Associated With Intensive Care Unit Pediatric Delirium in Children Younger Than 2 Years Old: A Single-Center Observational Study

Abstract: Objective: The primary objective of this study was to investigate the prevalence of intensive care unit (ICU) pediatric delirium in Shanghai, China. Secondary objectives were to determine the association of hypoxia and infection with ICU pediatric delirium, and the impact between different age. Design: Prospective single-center observational study. Setting: Two pediatric intensive care unit (PICU) within a tertiary-A general hospital. Patients: Patients age between 1 month to 7 years in PICU who stayed at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The PICU in this study was a multi-bed monitoring room where children were susceptible to light and noise pollution and parents could not visit, resulting in a lack of family participation. Ge et al 21 found that the prevalence of delirium in a hospital in Shanghai was 31.30%, which might be related to the different ages of the enrolled children and the different variables collected in the two studies. While a higher occurrence was reported in surgical patients, the prevalence of paediatric delirium in the paediatric cardiac ICU (PCICU) was as high as 67%, 6 which could be due to different types of diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PICU in this study was a multi-bed monitoring room where children were susceptible to light and noise pollution and parents could not visit, resulting in a lack of family participation. Ge et al 21 found that the prevalence of delirium in a hospital in Shanghai was 31.30%, which might be related to the different ages of the enrolled children and the different variables collected in the two studies. While a higher occurrence was reported in surgical patients, the prevalence of paediatric delirium in the paediatric cardiac ICU (PCICU) was as high as 67%, 6 which could be due to different types of diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Although Ge et al 21 have reported the incidence of delirium and its influencing factors in a PICU in China, the study population only covered children aged from 1 month to 7 years old. We designed a prospective study and included children of all ages in an attempt to comprehensively determine the incidence of delirium and the risk factors of delirium in critically ill children in a Chinese tertiary PICU.…”
mentioning
confidence: 99%